Incidence of Thyroid Cancer in Thyroid Swellings (Medical Forum Monthly, 2022)
Objective: To reduce the incidence of thyroid cancer among thyroid swelling, underwent thyroidectomies and to compare FNAC and histopathology reports.Study Design: Retrospective case series study.Place and Duration of Study: This study was conducted at the Department of General Surgery, Shaikh Zayed Hospital, Lahore from January 2018 to January 2021.Materials and Methods: One hundred and fifty cases were included of thyroid swelling. Histopathological and FNAC reports were considered to get incidence of benign and malignant cases among thyroid swellings.Results: Thyroid swelling patients were from 10-80 years and mean age was 39.3 years. 118 (78.66%) were females and 32 (21.33%) were males with 3.68:1 female to male ratio. Among 150 cases 142 cases were cytologically benign and 8 were malignant on FNAC based Bathesda category. On histopathology same results were observed as 142 cases benign and 8 cases were malignant (6 were female and 2 were males). However among benign lesions 95.77% were MNG on histopathological examination and 91.54% on FNAC and among malignant 75% (6 out of 8) were papillary thyroid CA.Conclusion: In this study no difference is observed between FNAC and histopathological examination, but histopathology of the specimen gives incidence of thyroid malignancy. Incidence of thyroid malignancy is 5.33% among thyroid swellings.